Analysis of Urinary Fibronectin Levels in Patients with Type 2 Diabetes Mellitus and Non-Diabetes Mellitus - Muh Anshar J; Liong Boy Kurniawan; Nurahmi Nurahmi; Andi Alfian Zainuddin; Husaini Umar; Mansyur Arif (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2023)
Diabetic nephropathy is a microvascular complication associated with high glucose levels in individuals with diabetes mellitus (DM). Fibronectin, an early marker of diabetic nephropathy, can indicate the occurrence and progression of renal damage. This cross-sectional study aimed to compare urinary fibronectin levels in patients with type 2 diabetes mellitus and non-diabetes mellitus. A sample of 50 DM patients was divided into two groups: the DM group and the non-DM group. Urinary fibronectin levels were measured using the ELISA method, while albuminuria levels were determined by the albumin-to-creatinine ratio (ACR). Statistical analysis was performed to assess the relationship between urinary fibronectin levels and urine albumin. Results: The average urinary fibronectin level in DM patients was 2.07 ± 3.04 ng/mL, which was slightly higher than the level observed in non-DM patients (1.09 ± 0.56 ng/mL). However, this difference was not statistically significant (p 0.05). Additionally, there was no significant relationship found between urinary fibronectin levels and urine albumin (p = 0.001). Conclusion: The findings of this study indicate that urinary fibronectin levels in individuals with DM were slightly higher than those without DM. However, this difference did not reach statistical significance. The lack of a significant relationship between urinary fibronectin levels and urine albumin suggests that fibronectin may provide additional information about renal damage in DM patients, independent of albuminuria. Further research is necessary to explore the clinical significance of urinary fibronectin as a potential biomarker for diabetic nephropathy.